Control of the electrical resistivity of Ni-Cr wires using low pressure chemical vapor deposition of tin - Kim, Jun Hyun; Bak, Jeong Geun; Lee, Kangtaek; Kim, Chang Koo (Applied Surface Science, 2018)
Control of the electrical resistivity of Ni-Cr wires is demonstrated using low pressure chemical vapor deposition (LPCVD) of tin on the surface of the wire, after which the effects of the deposition temperature on the structural, morphological, and compositional characteristics of the tin-deposited Ni-Cr wires are investigated. As the deposition temperature is increased, the resistivity of the Ni-Cr wires increases in the temperature range 300–400 °C; then remains nearly constant as the temperature increased to 700 °C. The increase in the resistivity of the Ni-Cr wires is attributed to formation of Ni 3 Sn 2 particulates on the surface of the wire. Compositional analysis shows that the pattern of change in the tin content with the deposition temperature is similar to that of resistivity with temperature, implying that the atomic content of tin on Ni-Cr directly affects the electrical resistivity.
Keywords: Compositional analysis; Compositional characteristics; Deposition temperatures; LPCVD; Temperature range; Tin content; Electrical resistivity; Fusible resistors; LPCVD; Ni-Cr wires; Tin